Hubungan Stres dan Pola Makan dengan Kejadian Gastritis pada Remaja di SMA Swasta Bina Siswa - Barasa, Bilson; Simanullang, Rostime Hermayerni (Pustaka Galeri Mandiri, 2025)
Stress and poor diet can affect the occurrence of gastritis. Adolescence is a crucial period in physical and psychological development, so it can trigger stress and irregular eating patterns that cause gastritis. Objective To determine whether there is a relationship between stress and eating patterns with the occurrence of gastritis in adolescents at Bina Siswa Private High School. Method This type of research is quantitative with descriptive correlation design using a Cross-sectional approach. The research sample involved 58 students selected using total sampling. Data were collected through a questionnaire perceived stress scale (PSS), a questionnaire diet, Gastritis questionnaire. Statistical tests using statistical tests using Spearman's rho to analyze the relationship between the two variables. The results showed that stress is the most influential variable on the incidence of Gastritis in SMASwasta Bina Siswa. The value of Exp (B) = 4.667 indicates that students who experience stress have a 4.667 times greater risk of experiencing Gastritis compared to students who do not experience stress. This is supported by a significance value that meets the requirements (p <0.05). Conclusion there is a significant relationship between stress levels and diet with the incidence of gastritis in adolescents at SMA Swasta Bina Siswa. Therefore, it is recommended that schools need to integrate educational programs on stress management and healthy eating patterns into the curriculum, seminars, and extracurricular activities that support students' mental and physical health.